Belgium : Selected Issues. (IMF Staff Country Reports; Country Report, 2001)
This paper provides a number of complementary estimates of potential output and the output gap-variables that cannot be observed directly. After a substantial increase in the tax wedge in the 1970s and the 1980s, which has been widely thought to have been partly responsible for the sharp rise in unemployment rates, the Belgian authorities instituted a policy of reduction in employers' social security contributions. The reforms will reverse the increase in average income tax rates during the 1990s.